2007
DOI: 10.1074/jbc.m606885200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interleukin (IL)-6 Inhibitor IL-6-RFP

Abstract: Although fusion proteins of the extracellular parts of receptor subunits termed cytokine traps turned out to be promising cytokine inhibitors for anti-cytokine therapies, their mode of action has not been analyzed. We developed a fusion protein consisting of the ligand binding domains of the IL-6 receptor subunits IL-6R␣ and gp130 that acts as a highly potent IL-6 inhibitor. Gp130 is a shared cytokine receptor also used by the IL-6-related cytokines oncostatin M and leukemia inhibitory factor. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Extracellular acidification inhibits IL1 β production showed improved cell environment and reduce acidosis, suggested a protective effect of chronic neurodegenerative diseases ( Jin et al, 2014 ). IL6 has been proved as a target for the treatment of several inflammatory diseases ( Metz et al, 2006 ). Recently, several new IL1 and IL6 inhibitors were developed and their therapeutic effects have been successfully validated ( Divithotawela et al, 2016 ; Wiesinger et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular acidification inhibits IL1 β production showed improved cell environment and reduce acidosis, suggested a protective effect of chronic neurodegenerative diseases ( Jin et al, 2014 ). IL6 has been proved as a target for the treatment of several inflammatory diseases ( Metz et al, 2006 ). Recently, several new IL1 and IL6 inhibitors were developed and their therapeutic effects have been successfully validated ( Divithotawela et al, 2016 ; Wiesinger et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through this so-called “trans-signaling” mechanism, IL-6 is capable of stimulating cells that lack endogenous mIL-6R [ 38 ]. Additionally, it has been shown that the soluble form of gp130 (sgp130) exclusively inhibits IL-6 responses mediated via the IL-6/sIL-6R complexes (i.e., trans-signaling) and does not affect stimulation via mIL-6R (i.e., classical IL-6 signaling) [ 39 41 ]. Therefore, sgp130 can be used as a molecular tool to discriminate between classical signaling and trans-signaling.…”
Section: Introductionmentioning
confidence: 99%
“…This stoichiometry is analogous to the high-affinity hexameric receptor complex consisting of two molecules of each IL-6, sIL-6R α and gp130 that has been verified by X-ray crystallography 16 . Earlier work demonstrated that IL-6-RFP indeed forms complexes similar to the native IL-6 receptor complex 39 . The extraordinary inhibitory potency of mIL-6-RFP-Fc is demonstrated by its capacity to inhibit IL-6-mediated proliferation of Ba/F3-mgp130/mIL-6R α cells with a tenfold higher potency than the original mIL-6-RFP.…”
Section: Discussionmentioning
confidence: 95%